Technical change directions of China’s grain production: application of the bias-corrected Malmquist indices - Li, Tianxiang; Baležentis, Tomas; Cao, Lijuan; Zhu, Jing; Štreimikienė, Dalia; Melnikienė, Rasa (Technological and Economic Development of Economy, 2018)
This paper aims at measuring productivity and efficiency of China’s three most important grain crops–rice, wheat and maize–as well as identifying the main directions of technical change prevailing in their production. The bias-corrected Malmquist production indices are employed to measure the technical changes (TCs) in terms of input-saving or input-using in China’s grain production, by using provincial aggregate data obtained from the National Farm Production Costs and Returns Survey. The research covers the period of 2003–2013. Application of the bias-corrected Malmquist index showed a labor-saving technical change against all the remaining inputs for the three crops under analysis. The highest frequencies of fertilizer- and machinery-using, labor-saving technical changes were observed for wheat farming. Therefore, a reduction in labor intensity should be the most promising for wheat if compared with rice and maize.